Identifikasi Jenis Satwa Liar yang Dimanfaatkan secara Komersial dan Non-Komersial di Provinsi Nusa Tenggara Timur - Stefani Angela Nainupu; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2024)
This study has been carried out in the area of East Nusa Tenggara Province. The study aims to find out the types. The method used in this study is the qualitative method. The results of the study obtained through the interview method. The results of the study were obtained as many as 2 types of wildlife that were used commercially for the purpose of business licenses and as many as 28 types of wildlife that were used non-commercially for the purpose of breeding, research and souvenirs. The conservation status of commercially exploited and non-commercial wildlife according to PERMEN HUT No. 106 of 2018, there are 7 protected species, according to IUCN there are 15 species including LC (Least Concern) category, 2 types including VU (Vulnerable) category, 2 types including category EN (Endangered), 1 type including CR (Critically Endangered) category, and 1 type including NT (Near Threatened) category, according to CITES there is 1 species included in Appendix I and 3 types that include Appendix II.